A High Neutrophil-to-Lymphocyte Ratio Predicts Higher Risk of Poststroke Cognitive Impairment: Development and Validation of a Clinical Prediction Model - Zha, Fei; Zhao, Jingjing; Chen, Cheng; Ji, Xiaoqi; Li, Meng; Wu, Yinyin; Yao, Li (Frontiers in Neurology, 2022)
Objective: Poststroke cognitive impairment (PSCI) is a serious complication of stroke. The neutrophil to lymphocyte ratio (NLR) is a marker of peripheral inflammation. The relationship between the NLR and PSCI is far from being well studied, and the thesis of this study was to assess the predictive value of the NLR in patients with PSCI, and establish and verify the corresponding prediction model based on this relationship. Methods： A total of 367 stroke patients were included in this study. Neutrophils, lymphocytes, and the NLRs were measured at baseline, and clinical and neuropsychological assessments were conducted three months after stroke. The National Institutes of Health Scale (NIHSS) was used to assess the severity of stroke. A Chinese version of the Mini Mental State Examination (MMSE) was used for the assessment of cognitive function assessment. Results: After three months of follow-up, 87 (23.7%) patients were diagnosed with PSCI. The NLR was significantly higher in PSCI patients than in non-PSCI patients (P < 0.001). Patient age, sex, body mass index, NIHSS scores and high-density lipoprotein levels also differed in the univariate analysis. In the logistic regression analysis, the NLR was an independent risk factor associated with the patients with PSCI after adjustment for potential confounders (OR =1.67, 95%CI:1.21-2.29, P=0.002). The nomogram based on patient sex, age, NIHSS score and the NLR had good predictive power with an AUC of 0.807. In the validation group the AUC was 0.816. Conclusion: An increased NLR at admission is associated with PSCI, and the model built with the NLR as one of the predictors can increase prognostic information for the early detection of PSCI.